A Systematic Review of Psychological Interventions for Adult and Pediatric Patients with Vocal Cord Dysfunction - Guglani, Loveleen; Atkinson, Sarah; Hosanagar, Avinash; Guglani, Lokesh (Frontiers in Pediatrics, 2014)
Background: Vocal Cord Dysfunction (VCD) or Paradoxical Vocal Fold Motion (PVFM) is a functional disorder of the vocal cords that requires multidisciplinary treatment. Besides relaxation techniques, the use of psychological interventions can help treat the underlying psychological co-morbidities. There is currently no literature that examines the effectiveness of psychological interventions for VCD/PVFM. Objectives: To review the evidence for psychological interventions used for the treatment of patients with VCD/PVFM. Data Sources: We searched electronic databases for English medical literature using Pubmed (Medline), PsycInfo, Cochrane Database of Systematic Reviews, Cochrane Central Registry of Controlled Trials and Clinicaltrials.gov. The date range for our search is from July 1963 to July 2013. Study Eligibility Criteria, Participants and Interventions: We included studies that reported the use of psychological interventions in both adults and children diagnosed with VCD/PVFM. We included randomized controlled trials, case-control studies, retrospective chart reviews, prospective case series, and individual case reports. Results: Most reported studies are small case series or individual case reports that have described the use of interventions such as psychotherapy, behavioral therapy, use of anti-anxiety and anti-depressant medications, and hypnotherapy in conjunction with breathing exercises taught by speech therapists for symptomatic relief. Among the various psychological interventions that have been reported, there is no data regarding effectiveness and/or superiority of one approach over another in either adult or pediatric patients. Conclusions: Psychological interventions have a role to play in the management of adult and pediatric patients with VCD/PVFM. Future prospective studies using uniform approaches for treatment of associated psychopathology may help address this question. Systematic Review Registration Number: CRD42013004873 (PROSPERO)